Detection of serum anti-B/B' UsnRNP antibodies in patients with connective tissue diseases by immunoblotting - A. Ghirardello; A. Doria; S. Zampieri; D. Villalta; R. Tozzoli; L. Iaccarino; R. Bendo; P.F. Gambari (PAGEPress Publications, 2002)
Objective: To investigate the reliability of the immunoblot method in the detection of serum immunoreactivity towards the B/B' polypeptides of U small nuclear ribonucleoproteins (UsnRNP) and to assess the significance of these antibodies in connective tissue disease (CTD) patients. Methods: We tested the sera of 348 patients with CTD (101 SLE, 51 systemic sclerosis, 53 primary Sjogren's syndrome, 27 poly/dermatomyositis, 15 rheumatoid arthritis and 101 overlap CTD), of 31 matched healthy subjects and 13 patients with primary Epstein-Barr virus (EBV) infection with high titre IgG anti-EBV antibodies. IgG anti-UsnRNP antibodies were determined by immunoblotting on nuclear extract from Raji cells (an EBV-immortalised human B lymphoid cell line) and Jurkat cells (a human T lymphoid cell line). Anti-dsDNA antibodies were detected by indirect immunofluorescence on Crithidia luciliae and anti-ENA by counterimmunoelectrophoresis. Anti-dsDNA activity and avidity were measured in SLE sera by ELISA with Scatchard analysis. Results were statistically analysed by chi-square and Mann-Whitney tests. Results: A high frequency of anti-B/B' antibodies was found in the sera of CTD patients, confined to SLE (54.4%) and overlap CTD with SLE features (55,2%). Anti-B/B' immune reactivity was closely associated with other anti-UsnRNP specificities, gel precipitating anti-nRNP and anti-P antibodies. Nine out of 15 (60%) anti-B/B' positive/anti-ENA negative lupus sera on Raji blots were confirmed to be positive also on Jurkat blots. The sera from patients with EBV infection provided, on Raji blots, completely different band patterns from those obtained with auto-immune sera. Conclusions. The Sm B/B' proteins are the predominant or, at least, the most frequently targeted antigens of the UsnRNP auto-immune response in SLE and "lupus-like" overlap CTD. Moreover, anti-B/B' is diagnostically specific for CTD with SLE features. Immunoblotting on human B lymphoid cells is a reliable method, in terms of sensitivity and specificity, for the detection of anti-Sm B/B' antibodies.